Sodium ion battery negative plate and sodium ion battery

By coating multiple layers of carbon-containing active substances and conductive metal nanowires on the negative electrode sheet of the sodium ion battery, the reduction of conductivity and mechanical performance problems caused by the increase in electrode thickness are solved, and the energy density of the sodium ion battery is increased and the cost of the kilowatt-hour is reduced.

CN119673960APending Publication Date: 2025-03-21SO-FUN TECH CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411801859.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing sodium ion batteries have a longer ion and electron transport path due to the increase in electrode thickness, resulting in a longer migration time, resulting in a decrease in charge and discharge rate performance. At the same time, the high electrode thickness increases the slurry coating thickness, resulting in cracking, uneven thickness and reduced bonding stability.

Method used

By simultaneously coating several layers of carbon-containing active substances on at least one side of the current collector of the sodium ion battery negative electrode sheet, the resistivity and adhesion of the diaphragm are controlled, and conductive metal nanowires are added to the non-surface diaphragm to improve the conductivity of electrons and ionic ions and improve the adhesiveness and flexibility of the electrode sheet.

Benefits of technology

The electronic and ionic conductivity of the negative electrode sheet is improved, the mechanical strength and flexibility of the electrode sheet is enhanced, the energy density of the sodium ion battery is improved, the cost of kilowatt-hour is reduced, and good magnification and cycling performance are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673960A_ABST
    Figure CN119673960A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery negative electrode plate, which comprises a current collector and a plurality of layers of diaphragms arranged on at least one side of the current collector, the number of layers of the diaphragms is not less than two, the plurality of layers of diaphragms are sequentially superposed, and the resistivity of the plurality of layers of diaphragms is reduced from the diaphragm on the outermost layer to the diaphragm on the innermost layer; the stripping force of the plurality of membranes on the current collector metal foil is increased from the membrane on the outermost layer to the membrane on the innermost layer; a conductive metal nanowire is arranged in at least one of the membranes which are not on the outermost layer; the invention also discloses a sodium ion battery. According to the sodium-ion battery negative plate provided by the invention, the surface of at least one side of the current collector is simultaneously coated with a plurality of layers of carbon-containing active substances, and the electronic and ionic conductivity of the negative plate is improved and the bonding force and flexibility of the negative plate are improved by controlling the resistivity of a plurality of layers of diaphragms and the bonding force of a material layer and adding a conductive metal nanowire in a non-topmost diaphragm; therefore, the active substance loading capacity of the positive and negative plates in unit area is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery negative electrode sheet and a sodium ion battery. Background Art

[0002] In recent years, smart electric bicycles, low-speed electric vehicles, household energy storage cabinets, energy storage power stations, park / scenic area sightseeing electric vehicles, etc. with sodium-ion batteries as the "heart" have been continuously launched, and the application of sodium-ion batteries has become more and more extensive. Although the cost of raw materials for sodium-ion batteries is lower than that of lithium-ion batteries, the energy density of sodium-ion batteries is also lower than that of lithium-ion batteries, resulting in a larger amount of auxiliary materials such as aluminum foil, diaphragms, and shells used in sodium-ion batteries, which makes the cost per kilowatt-hour of sodium-ion batteries not advantageous. By increasing the thickness of the electrode coating, the amount of aluminum foil and diaphragm used on a single battery cell can be reduced, thereby increasing the energy density of the sodium-ion battery and reducing the cost per kilowatt-hour. The existing common electrode is to prepare the electrode material into a slurry, coat it on the current collector, and prepare it into a dry electrode by heating and drying the solvent. Directly increasing the electrode thickness will cause the transmission path of ions and electrons to become longer, and the migration time will be longer, which will cause the charge and discharge rate performance to decrease; at the same time, high electrode thickness means high slurry coating thickness. On the one hand, due to the slurry casting problem, cracking, uneven thickness, or reduced bonding stability will occur. In addition, since the surface solvent evaporates first during the drying process, the glue below floats with the solvent, resulting in reduced adhesion of the inner film and reduced mechanical properties. At present, the methods for increasing coating thickness include infiltration method, magnetic assisted molding, template method, and 3D printing, but the above methods are complex and costly, and the pole piece structure still needs to be designed to solve the electron / ion transmission problem. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a sodium ion battery negative electrode sheet and a sodium ion battery, wherein several layers of carbon-containing active material are simultaneously coated on at least one side of the current collector, and the electronic and ionic conductivity of the negative electrode sheet is improved, and the electrode sheet adhesion and flexibility are improved by controlling the resistivity of several layers of membranes and the adhesion of material layers, and adding conductive metal nanowires to non-topmost membranes, thereby increasing the active material loading per unit area of ​​the positive and negative electrode sheets.

[0004] The technical solution provided by the present invention is as follows: A sodium ion battery negative electrode sheet comprises a current collector and a plurality of membrane sheets arranged on at least one side of the current collector, wherein the number of membrane sheets is not less than two, the plurality of membrane sheets are stacked in sequence, the resistivity of the plurality of membrane sheets decreases from the outermost membrane sheet to the innermost membrane sheet; the peeling force of the plurality of membrane sheets on the current collector metal foil increases from the outermost membrane sheet to the innermost membrane sheet; and at least one of the membrane sheets not being the outermost membrane sheet is provided with conductive metal nanowires.

[0005] Preferably, the ratio between the resistivity of the outermost membrane and the resistivity of the innermost membrane is 3:1 to 1:1; wherein the resistivity of the innermost membrane is 0.05 to 0.30 Ω·cm.

[0006] Preferably, the ratio between the peeling force of the outermost membrane sheet on the current collector metal foil and the peeling force of the innermost membrane sheet on the current collector metal foil is 1:1.5 to 1:20; wherein the peeling force of the innermost membrane sheet on the current collector metal foil is 0.2 to 4 N / 30 mm.

[0007] Preferably, the ratio between the thicknesses of adjacent membranes is 1:4 to 4:1; wherein the thickness of the innermost membrane is 20 to 200 μm.

[0008] Preferably, the amount of the conductive metal nanowires added to the membrane is 0.5-10% of the total mass of the membrane.

[0009] Preferably, the conductive metal nanowire has a diameter of 50 to 5000 nm and a length of 0.1 to 100 μm.

[0010] Preferably, the conductive metal nanowire is an aluminum-containing nanowire, which includes one or a combination of pure metal aluminum wire and composite metal aluminum wire. The aluminum-containing nanowire is cheap, light, has good mechanical properties, and does not react with sodium to form an alloy, and is the best choice. Other conductive metal nanowires, such as copper-containing nanowires, silver-containing nanowires, etc., can also achieve the effects that aluminum-containing nanowires can achieve, but they are more expensive and heavier, and are not the best choice.

[0011] Preferably, the several layers of the membrane are prepared by mixing carbon-containing active substances and a binder; the carbon-containing active substances include hard carbon or soft carbon, and the binder is one or more combinations of polyvinylidene fluoride, polyacrylonitrile, sodium polyacrylate, and styrene-butadiene rubber.

[0012] A sodium ion battery, comprising the above-mentioned sodium ion battery negative electrode sheet, wherein the negative electrode of the sodium ion battery negative electrode sheet is obtained by rolling and sheeting, and the density of the non-foil area of ​​the rolled thick negative electrode is 0.9-1.1 g / cm 3 , combined with a positive electrode, a separator, and an electrolyte to form a sodium-ion battery.

[0013] The sodium ion battery negative electrode sheet of the present invention has different designs for several layers of membrane sheets on one side of the current collector. Firstly, the conductivity of the electrode is gradually improved from top to bottom, and the inner membrane sheet can provide a conductive channel for the surface membrane sheet, thereby improving the rate and preventing sodium precipitation caused by insufficient negative electrode dynamics; secondly, the adhesion of the electrode is gradually improved from the inside to the outside, which supplements the floating phenomenon of the glue solution, enhances the adhesion between the inner membrane sheet and the current collector, and improves the mechanical strength of the electrode sheet.

[0014] The present invention has the following advantages over the prior art: The negative electrode sheet of the sodium ion battery of the present invention is coated with several layers of carbon-containing active material on at least one side of the current collector. By controlling the resistivity of several layers of membranes and the adhesion of material layers, and adding conductive metal nanowires to the non-topmost membrane sheets, the electronic and ionic conductivity of the negative electrode sheet is improved, and the adhesion and flexibility of the electrode sheet are improved. By adding conductive metal nanowires to at least one layer of the non-topmost membrane sheets, a linear conductive network is constructed to improve the electronic conductivity of the inner membrane sheet; and relying on the mechanical properties of the conductive metal nanowires, the casting of the inner slurry is improved, and the adhesion of the membrane to the current collector and the flexibility of the membrane are improved. The single-sided surface density of the negative electrode sheet of the sodium ion battery of the present invention is increased to 10-20 mg / cm 2 , the single-sided thickness is increased to 120-240 μm, and the electrode sheet does not drop. Compared with the conventional thickness electrode sheet, the sodium ion battery negative electrode sheet of the present invention has the same electronic conductivity and ion conductivity, and the prepared sodium ion battery has the same electrical performance, and the energy density is increased by 10%. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 Schematic diagram of coating of a negative electrode sheet of a sodium ion battery in an embodiment of the present invention; Figure 2 The appearance diagram of the negative electrode sheet of Example 1 and Comparative Example 1 of the present invention; Figure 3 The normal temperature cycle life diagram of the sodium ion batteries prepared in Examples 1-5 and Comparative Examples 1, 2, and 4; Figure 4 Graph showing the peeling force of different dry films on aluminum foil in Example 1 of the present invention.

[0017] Reference numerals: 1. Aluminum foil; 2. Slurry 1; 3. Slurry 2; 4. Coating die head. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0019] Embodiment 1: The embodiment of the present invention provides a negative electrode sheet for a sodium ion battery, such as Figure 1 As shown, it includes a current collector and several layers of membranes arranged on the surfaces of both sides of the current collector. Specifically, two layers of membranes are arranged on each side surface. The metal foil of the current collector is aluminum foil 1. The two layers of membranes are stacked in sequence. The resistivity of the two layers of membranes decreases from the surface membrane 3 (i.e., the first layer of membrane described below) to the inner membrane 2 (i.e., the second layer of membrane described below); the peeling force of the two layers of membranes on the aluminum foil increases from the surface membrane 3 to the inner membrane 2; and aluminum nanowires are arranged in the inner membrane 2. The inner membrane 2 is close to the aluminum foil 1 and needs better conductivity, which can provide a better electron channel for the surface membrane 3, so that the electron transmission resistance of the pole piece is reduced, and the battery rate and cycle performance can be improved. The aluminum nanowires not only have excellent conductivity, but also have stable chemical properties and good mechanical properties. Therefore, adding the inner membrane can significantly reduce the resistivity, improve the conductivity, and improve the flexibility and mechanical strength of the pole piece. On the other hand, assuming that the aluminum-containing nanowires are set on the surface film and in contact with the diaphragm, it is easy to pierce the diaphragm and cause a short circuit, or cause high self-discharge of the battery cell due to the tip discharge effect.

[0020] like Figure 1As shown, the preparation process of the negative electrode sheet of the sodium ion battery is as follows: hard carbon: conductive carbon: nano-aluminum wire: styrene-butadiene rubber (SBR): CMC are mixed in pure water at a ratio of 91.5:2.0:2.0:4.0:0.5 to obtain slurry 1, which is used as the second layer of membrane slurry. Hard carbon: conductive carbon: SBR: CMC are mixed in pure water at a ratio of 97:1:1:1 to obtain slurry 2, which is used as the first layer of membrane slurry. Among them, the dry film obtained by slurry 1 has an internal resistance of 0.10Ω·cm, and the peeling strength with aluminum foil is 1N / 30mm. The dry film obtained by slurry 2 has an internal resistance of 0.20Ω·cm, and the peeling strength with aluminum foil is 0.1N / 30mm. For the internal resistance of the membrane, the ratio of the first membrane to the second membrane is 2:1; for the peeling force of the membrane to the aluminum foil, the ratio of the first membrane to the second membrane is 1:10. Slurry 1 and slurry 2 are simultaneously coated on one side of the aluminum foil 1 through the coating die 4 of the double-layer coating machine, slurry 1 is on the inner film, slurry 2 is on the surface film, and dried to obtain a single-sided thick coated negative electrode sheet. Then, the same method is used to coat the other side of the aluminum foil 1, and dried to obtain a double-sided thick coated negative electrode sheet. The thickness of the first layer of the film: the second layer of the film is controlled to be 3:1, the thickness of the second layer of the film is 40μm, and the thickness of the first layer of the film is 120μm. The density of the negative electrode after rolling is 1.0g / cm 3 .

[0021] The test method of the peeling force of the negative electrode membrane of the sodium ion battery on the aluminum foil in this embodiment is as follows: 1. Cutting the electrode: Take the electrode after rolling, and use a customized knife die to cut the electrode, generally 400mm long and 30mm wide. 2. Pasting and fixing the electrode: Take a flat thin steel plate, about 300mm long and 50mm wide; first stick a double-sided tape on the center of the steel plate (the length is greater than the sample test length, and the same width as the electrode), smooth it with force to ensure that the double-sided tape is tightly attached to the center of the steel plate, peel off the double-sided tape, and stick the electrode on the tape. It must be ensured that the electrode and the tape are matched and fitted. 3. Installation test: On the tensile machine, insert the steel plate with the fixed electrode into the lower clamp and fix it vertically; insert the un-adhesive electrode into the upper clamp and fix it, so that the electrode attached to the tape is 180° with the electrode fixed by the upper clamp. After fixing the test sample, first calibrate and reset, set the test width to 30mm, the electrode peeling length to 50-150mm, the peeling speed to 50-100mm / min, and then start the test to obtain the peel strength curve and average value. Figure 4 shown.

[0022] The test method for the internal resistance of the dry film made of slurry 1 and slurry 2 in this embodiment (the internal resistance is a direct reading. The internal resistance of the dry film of slurry 1 is 0.10Ω·cm, and the internal resistance of the dry film of slurry 2 is 0.20Ω·cm) is as follows: 1. Film preparation: Use a 150μm thick scraper to coat the slurry on the surface of the PET film, and then transfer it to a 100℃ oven for drying. 2. Test: Cut the dried film into discs with a diameter of 55mm, record the dry film thickness, and use the four-probe method to test the internal resistance of the film in the material area.

[0023] A sodium ion battery comprises the above-mentioned sodium ion battery negative electrode sheet, and its preparation method comprises: winding, packaging, injecting and forming a Prussian blue positive electrode sheet, the above-mentioned sodium ion battery negative electrode sheet and a diaphragm into a battery core, so as to obtain a sodium ion battery.

[0024] Embodiment 2: Slurry 1 and slurry 2 are the same as Example 1. Hard carbon: conductive carbon: nano-aluminum wire: styrene-butadiene rubber (SBR): CMC are mixed in pure water at a ratio of 94.5.0:1.0:1.0:3.0:0.5 to obtain slurry 3. The dry film prepared by slurry 3 has an internal resistance of 0.15Ω·cm and a peel strength with aluminum foil of 0.3N / 30mm.

[0025] Slurry 1, slurry 2 and slurry 3 are simultaneously coated on aluminum foil through a multi-layer coating machine, with slurry 1 on the lower layer, slurry 2 on the upper layer, and slurry 3 on the middle layer, and dried to obtain a negative electrode sheet (this embodiment is also a double-sided coated negative electrode sheet). Control the upper layer thickness: middle layer thickness = 3:1, middle layer thickness: lower layer thickness = 2:1. The bottom layer membrane thickness is 20μm, the middle layer membrane thickness is 40μm, and the upper layer membrane thickness is 120μm. The negative electrode density after rolling the electrode sheet is 1.0g / cm 3 .

[0026] The above settings satisfy that the ratio between the resistivity of the outermost film and the resistivity of the innermost film is 2:1, and the resistivity of the film decreases from the outermost layer to the innermost layer; the ratio of the peeling force of the film on the aluminum foil is 1:10, and the resistivity of the film increases from the outermost layer to the innermost layer.

[0027] Embodiment 3: According to Example 1, the formula of slurry 1 and 2 was adjusted so that the internal resistance of the dry film prepared by slurry 1 was 0.10Ω·cm, and the peel strength with aluminum foil was 1.0N / 30mm. The internal resistance of the dry film prepared by slurry 2 was 0.30Ω·cm, and the peel strength with aluminum foil was 0.1N / 30mm. For the internal resistance of the film, the ratio of the first film layer to the second film layer was 3:1; for the peel strength of the film to the aluminum foil, the ratio of the first film layer to the second film layer was 1:10.

[0028] Embodiment 4: According to Example 1, the formula of slurry 1 and 2 is adjusted so that the dry film obtained by slurry 1 has an internal resistance of 0.10Ω·cm and a peel strength of 0.15N / 30mm with aluminum foil. The dry film obtained by slurry 2 has an internal resistance of 0.20Ω·cm and a peel strength of 0.1N / 30mm with aluminum foil. For the internal resistance of the film, the ratio of the first film layer to the second film layer is 2:1; for the peel strength of the film to the aluminum foil, the ratio of the first film layer to the second film layer is 1:1.5.

[0029] Embodiment 5: In this embodiment, the current collector metal foil is copper foil, and the rest is the same as that in Embodiment 1.

[0030] Embodiment 6: In this embodiment, the conductive metal nanowires are silver-containing nanowires, and the rest are the same as in Embodiment 1.

[0031] Embodiment 7: In this embodiment, the current collector is provided with several layers of membrane only on one side. For example, the corresponding slurry is coated on one side of the current collector according to the operation of Example 1 to obtain a single-sided thick-coated negative electrode sheet, which can also achieve the purpose of the present invention.

[0032] Comparative Example 1: The slurry of the first and second membrane layers are both slurry 2 in Example 1, and the rest are the same as Example 1.

[0033] Comparative Example 2: According to Example 1, the formulas of slurries 1 and 2 are adjusted so that the internal resistance of the dry film prepared by slurry 1 is 0.20Ω·cm, and the peel strength with aluminum foil is 1.0N / 30mm. The internal resistance of the dry film prepared by slurry 2 is 0.10Ω·cm, and the peel strength with aluminum foil is 0.1N / 30mm. For the internal resistance of the membrane, the ratio of the first membrane layer to the second membrane layer is 1:2; for the peel strength of the membrane to the aluminum foil, the ratio of the first membrane layer to the second membrane layer is 1:10.

[0034] Comparative Example 3: According to Example 1, the formulas of slurries 1 and 2 are adjusted so that the internal resistance of the dry film prepared by slurry 1 is 0.10Ω·cm, and the peel strength with aluminum foil is 0.2N / 30mm. The internal resistance of the dry film prepared by slurry 2 is 0.20Ω·cm, and the peel strength with aluminum foil is 2.0N / 30mm. For the internal resistance of the membrane, the ratio of the first membrane layer to the second membrane layer is 2:1; for the peel strength of the membrane to the aluminum foil, the ratio of the first membrane layer to the second membrane layer is 10:1.

[0035] Comparative Example 4: According to Example 1, the formula of slurry 1 and 2 is adjusted, and the nano aluminum wire of slurry 1 is removed, so that the internal resistance of the dry film prepared by slurry 1 is 0.10Ω·cm, and the peeling strength with aluminum foil is 1.0N / 30mm. The internal resistance of the dry film prepared by slurry 2 is 0.20Ω·cm, and the peeling strength with aluminum foil is 0.1N / 30mm. For the internal resistance of the film, the ratio of the first film layer to the second film layer is 2:1; for the peeling force of the film to the aluminum foil, the ratio of the first film layer to the second film layer is 1:10.

[0036] Compared with the comparative example 1, the appearance of the pole pieces of the embodiment 1 and the comparative example 1 is as follows: Figure 2 As shown, the appearance of Example 1 is good, without powder or material falling off, and the pole piece can be bent and rolled. However, the pole piece of Comparative Example 1 has the phenomenon of active material peeling off, and cannot be processed continuously.

[0037] The cycle performance of the sodium ion batteries prepared in Example 1 and Comparative Example 1 is as follows: Figure 3 In the 1C / 1C cycle process, the cell of Example 1 still has 80% capacity retention after 500 cycles, while the cell of Comparative Example 1 has only 60% capacity after 16 cycles. This shows that the cell processed from the negative electrode sheet of Example 1 has good rate charge and discharge performance.

[0038] Comparison between Example 1 and Comparative Example 1 shows that if no electrode design is performed and a slurry formulation is used to directly increase the coating thickness, it will lead to poor electrode appearance and sodium precipitation at the negative electrode.

[0039] Comparison between Example 1 and Comparative Example 2 shows that if the internal resistance of the first membrane layer is less than the internal resistance of the second membrane layer, sodium precipitation will occur at the negative electrode.

[0040] Comparison between Example 1 and Comparative Example 3 shows that if the peeling force of the first film layer is greater than the peeling force of the second film layer, the electrode sheet will have a poor appearance and cannot be processed.

[0041] Comparison between Example 1 and Comparative Example 3 shows that if the second layer of the diaphragm does not use nano-aluminum wires, the mechanical properties of the pole piece will deteriorate, and the cycle performance will deteriorate.

[0042] The comparison results of the electrode appearance, 180° bending of the electrode and the battery cell cycle conditions of Examples 1-7 and Comparative Examples 1-4 are shown in Table 1 below.

[0043] Table 1 Comparison results of the appearance of the pole pieces, the 180° bending of the pole pieces and the cell cycle conditions of Examples 1-7 and Comparative Examples 1-4

[0044] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A sodium ion battery negative electrode sheet, characterized in that: It comprises a current collector and several layers of membranes arranged on at least one side of the current collector, wherein the number of membrane layers is not less than two, and the several layers of membranes are stacked in sequence, and the resistivity of the several layers of membranes decreases from the outermost membrane to the innermost membrane; the peeling force of the several layers of membranes on the metal foil of the current collector increases from the outermost membrane to the innermost membrane; and at least one layer of the non-outermost membranes is provided with conductive metal nanowires.

2. The sodium ion battery negative electrode sheet according to claim 1, characterized in that: The ratio between the resistivity of the outermost membrane and the resistivity of the innermost membrane is 3:1 to 1:1; wherein the resistivity of the innermost membrane is 0.05 to 0.30 Ω·cm.

3. The negative electrode sheet for a sodium ion battery according to claim 1, characterized in that: The ratio between the peeling force of the outermost membrane sheet on the current collector metal foil and the peeling force of the innermost membrane sheet on the current collector metal foil is 1:1.5 to 1:20; wherein the peeling force of the innermost membrane sheet on the current collector metal foil is 0.2 to 4 N / 30 mm.

4. The negative electrode sheet for a sodium ion battery according to claim 1, characterized in that: The ratio between the thicknesses of adjacent membranes is 1:4 to 4:1; wherein the thickness of the innermost membrane is 20 to 200 μm.

5. The negative electrode sheet for a sodium ion battery according to any one of claims 1 to 4, characterized in that: The amount of the conductive metal nanowires added to the membrane is 0.5-10% of the total mass of the membrane.

6. The negative electrode sheet for a sodium ion battery according to claim 5, characterized in that: The conductive metal nanowire has a diameter of 50 to 5000 nm and a length of 0.1 to 100 μm.

7. The negative electrode sheet for a sodium ion battery according to claim 5, characterized in that: The conductive metal nanowires are aluminum-containing nanowires, and the aluminum-containing nanowires include pure metal aluminum wires and composite metal aluminum wires, or a combination of both.

8. The negative electrode sheet for a sodium ion battery according to any one of claims 1 to 4, characterized in that: The several layers of the membranes are all prepared by mixing carbon-containing active substances and binders; the carbon-containing active substances include hard carbon or soft carbon, and the binder is one or more combinations of polyvinylidene fluoride, polyacrylonitrile, sodium polyacrylate, and styrene-butadiene rubber.

9. A sodium ion battery, characterized in that: A sodium ion battery negative electrode sheet comprising the negative electrode sheet of any one of claims 1 to 8.